Implementasi Metode Al-Miftah Lil Ulum dalam Mengingkatkan Kemampuan Membaca Kitab Kuning pada Mahasantri di Pondok Pesantren Alquran (PPA) Ibnu Kastir Putra Jember - Ma'ruf, Ma'ruf (PAKAR Pendidikan, 2025)
The background of this research is based on the need to equip santri with the skills to interpret religious texts accurately, given the importance of the yellow book in Islamic education. This study examines the importance of religious knowledge in improving the understanding and practice of Islam, particularly through implementing the Al-Miftah Lil ‘Ulum method at PPA Ibnu Katsir Putra Jember. This method is used as a framework to improve the ability of students to read the yellow book. This research uses a qualitative case study approach with data collection techniques through observation, interviews, and documentation. The focus of this research is how the planning, implementation and evaluation of the implementation of the Al-Miftah Lil ‘Ulum method in improving the ability to read the yellowIslamic classic book (PPA) Putra Jember. The research subjects include educators and students involved in the Al-Miftah Lil ‘Ulum method learning program. The results showed that this method is effective in improving the ability to read and understand the yellowIslamic classic book. The process of planning, implementing and evaluating learning is carried out in a structured manner, so that it positively impacts the mastery of the students' Arabic language. This research concludes that a strong Arabic language skill base plays an important role in the mastery of religious knowledge, as well as emphasizing the relevance of traditional Islamic education in the contemporary era.